Estudo químico e ecológico de Escovopsis spp., invasor do jardim de fungos de formigas cortadeiras - Santos, Ana Carolina Alves do (2018)
Microorganisms associated to leaf cutting ants comprise an important source of antifungal and antibacterial compounds due to the environment they are inserted in. The fungal garden is composed by a complex microbial network in which, can be found, at least, a mutualistic fungus (Leucoagaricus gongylophorus), a specialized parasite (Escovopsis spp.), symbionts actinomycetes (Pseudonocardia and Streptomyces spp.) and many other microbes with still unknown ecological functions. Among these, we highlight the fungi belonging to the genus Escovopsis, due to their ability to bring nests to death when infected. In spite of its potential to produce antimicrobial agents, until now there is no reports about the chemical mediators produced by Escovopsis that are involved in this ecological relationship. Thus, aiming to better understanding the chemical-ecology of Escovopsis spp., two species from this genus (E. microspora and E. weberi) were investigated on their metabolomics and chemical-ecology aspects. Through metabolomics studies, it was possible to isolate and identify several secondary metabolites such as anthraquinones, aza-anthraquinones, polyketides, diketopiperazines, terpene-indole alkaloid, among others. On the other hand, coculture experiments between E. weberi and L. gongylophorus led to the isolation and identification of two compounds (melinacidin IV and shearinine D) which are upregulated in the presence of the symbiont fungus. Despite the fact they don’t display antifungal activity against L. gongylophorus, these metabolites inhibit the growth of bacteria responsible for the nest protection (Pseudonocardia spp.). Therefore, these substances may play a role in the ecological war between the microorganisms living in the leaf-cutting ants fungal garden.